(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Abstract Asset security and risk management are crucial for overall economic growth, and a country’s stability and populace safety depend on them running reliably and safely. For such a system, the assets’ proper operation is crucial, and any threats that could adversely affect the assets could cause serious disruption. Risk management is a crucial component of the safeguarding important infrastructure There are numerous approaches and frameworks for locating assets, calculating vulnerabilities, and analyzing vulnerabilities. The interdependencies between the assets, however, and the cascade effects of the assets’ innate weaknesses are not given enough attention. By introducing a fresh asset focus risk management method for the critical infrastructure, this research aims to close that gap. It offers a methodical approach for locating and analyzing vital assets, as well as any potential hazards or dangers to vital infrastructure. In our work, we consider how cascading vulnerability impacts on assets can pose risks and threaten users. To illustrate the applicability of the method, we utilize a running example from a smart grid system. Our findings demonstrate that certain assets are prioritized and more susceptible than others for the power grid system, which can have a significant negative influence on overall business continuity.